Mechanism of Rad51 filament formation by Rad52 and Rad55-Rad57 in homologous recombination - Jaigeeth Deveryshetty; Ayush Mistry; Sushil Pangeni; Mohamed Ghoneim; Monica Tokmina-Lukaszewska; Steven K. Gore; Jie Liu; Vikas Kaushik; Simrithaa Karunakaran; Angela Taddei; Wolf-Dietrich Heyer; Taekjip Ha; et al. (Nature Communications)
Abstract Homologous recombination (HR) repairs double-stranded DNA breaks (DSBs) by generating single-stranded DNA (ssDNA), which is initially coated by Replication Protein A (Rpa). Rad51, a recombinase, catalyzes strand invasion but binds ssDNA with lower affinity than Rpa, necessitating mediator proteins like Rad52 (yeast) or BRCA2 (humans) for Rad51 loading. The mechanisms of this exchange remain unclear. We show that Saccharomyces cerevisiae Rad52 uses its disordered C-terminus to sort polydisperse Rad51 into discrete monomers. Using fluorescent-Rad51 and single-molecule optical tweezers, we visualize Rad52-mediated Rad51 filament formation on Rpa-coated ssDNA, preferentially at ssDNA–dsDNA junctions. Deleting the C-terminus of Rad52 disrupts Rad51 sorting and loading. Addition of the Rad51 paralog Rad55–Rad57 enhances Rad51 binding by ~60%. Despite structural differences, Rad52 and BRCA2 share conserved functional features. We propose a unified “Sort, Stack & Extend” (SSE) mechanism by which mediator proteins and paralogs coordinate Rad51 filament assembly during HR.